2021
DOI: 10.1002/jum.15749
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Crown–Chin Length to Crown–Rump Length Ratio as a Prenatal Sonographic Marker for Triploidy at First Trimester

Abstract: Objectives-To investigate the ratio of Crown to Chin length (CCL) to Crown-rump length (CRL) between triploid and normal fetuses at first trimester and establish a reference range of fetal CCL/CRL ratio.Methods-Three hundred and twenty-five normal and 12 triploid fetuses were reviewed in this study. The image of fetal Crown-rump length (CRL) was acquired retrospectively. CCL and CRL were measured offline by two experienced sonographers, we obtained each averaged value of CCL and CRL as the final data for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Wang et al 12 suggested that the biparietal diameter/femur length (BPD/FL) ratio can predict thanatophoric dysplasia in the first trimester of pregnancy; it showed that the BPD/FL ratio increased in both 4 cases at first trimester and 20 cases at mid and third trimester. Recently, we reported 8 that the fetal CCL/CRL ratio increased significantly in triploid fetuses, which showed that the detection rate, false‐positive rate, and the positive likelihood ratio are 100, 5, and 20%. During the process of data review, we found that this ultrasound marker also increased in one fetus with skeletal dysplasia at 12 weeks of gestation, which showed short long bones, bowed femurs, omphalocele, and small thorax as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al 12 suggested that the biparietal diameter/femur length (BPD/FL) ratio can predict thanatophoric dysplasia in the first trimester of pregnancy; it showed that the BPD/FL ratio increased in both 4 cases at first trimester and 20 cases at mid and third trimester. Recently, we reported 8 that the fetal CCL/CRL ratio increased significantly in triploid fetuses, which showed that the detection rate, false‐positive rate, and the positive likelihood ratio are 100, 5, and 20%. During the process of data review, we found that this ultrasound marker also increased in one fetus with skeletal dysplasia at 12 weeks of gestation, which showed short long bones, bowed femurs, omphalocele, and small thorax as well.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the normal range of fetal CCL/CRL ratio in 325 singleton pregnancies with chromosomally normal fetuses. 8 Normal ranges in this study were based on the 325 normal fetuses used in our previous publication 8 and 93 normal new cases for a total of 418 fetuses. CCCL and CRL measurements were performed in the normal population and compared to measurements in fetuses with skeletal dysplasia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation